Climate resilience in agriculture: Key concepts for community-based adaptation - Gonsalves, Julian Francis; Vidallo, Rene R.; Monville-Oro, Emilita; Dalusag, Joanna B.; Barbon, Wilson John; Jordan, Jonna; Rosimo, Magnolia M.; Servano, Gonzalo S.; Lorenzo, Maria Cristina; Méndez, Kharla Vianca S.; Rosales, Belina O; Narte, Julieta; et al. (2016)
These primer was produced for a project under CCAFs, jointly implemented by the International Institute of Rural Reconstruction (IIRR), Philippines and the World Agroforestry Center (ICRAF), Vietnam Country Office. CCAFS Project No.: P55-FPI-SEA-ICRAF